A study of Modal analysis to determine the mechanical properties of materials - Fauziah, Mat; Zulkifli, M.J.; Othman I., M. N; Md Noor Arib, Md Rejab (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.